The Impact of Transportation Infrastructure on Women's Employment in India. Issue 4 (2nd October 2019) - Lei, Lei; Desai, Sonalde; Vanneman, Reeve
ABSTRACT: Indian women's labor force participation is extremely low, and women are much less likely than men to work in the nonfarm sector. Earlier research has explained women's labor supply by individual characteristics, social institutions, and cultural norms, but not enough attention has been paid to the labor market opportunity structure that constrains women's labor market activities. Using data from the India Human Development Survey (IHDS) in 2004–05 and 2011–12, this study examines how village transportation infrastructure affects women's and men's agricultural and nonagricultural employment. Results from fixed-effect analysis show that access by paved or unpaved roads and frequent bus services increase the odds of nonagricultural employment among men and women. The effect of road access on nonfarm employment (relative to not working) is stronger among women than among men. Improved transportation infrastructure has a stronger positive effect on women's nonfarm employment in communities with more egalitarian gender norms.